Neuro-Psycholinguistic Analysis of The Asbun Phenomenon among Generation Alpha on Tiktok - Virgin Noor Vadillah; Lusiana Suciati Dewi; Slamet Wahyudi Yulianto (Ma'soem University, 2026)
This study explores the phenomenon of ‘Asbun’ (speaking without real substance, or